2006
DOI: 10.1103/physrevb.74.121409
|View full text |Cite
|
Sign up to set email alerts
|

Edge-state signature in optical absorption of nanographenes: Tight-binding method and time-dependent density functional theory calculations

Abstract: The optical absorption of triangular nanographenes with well-defined edge structure, that is, zigzag-and armchair-type edges, is studied using the tight-binding method within the Hückel approximation. The absorption spectra of zigzag triangular nanographenes exhibit rich peak structures originating from the excitations associated with the edge states, while those of armchair ones do not. The main feature in the absorption spectra is reproduced by time-dependent density functional theory calculations within a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 17 publications
3
97
0
Order By: Relevance
“…3(a). The results are in good agreement with those of Yamamoto et al 39 Figure 3(b) presents the corresponding rð Þ=n tot for silicene QDs. The low-energy zoom at the inset to this figure reveals the shift of the 0.85 eV graphene peak toward 0.45 eV in silicene as a result of the decrease in the hopping energy.…”
Section: A Optical Absorption Of Triangular Quantum Dotssupporting
confidence: 82%
See 1 more Smart Citation
“…3(a). The results are in good agreement with those of Yamamoto et al 39 Figure 3(b) presents the corresponding rð Þ=n tot for silicene QDs. The low-energy zoom at the inset to this figure reveals the shift of the 0.85 eV graphene peak toward 0.45 eV in silicene as a result of the decrease in the hopping energy.…”
Section: A Optical Absorption Of Triangular Quantum Dotssupporting
confidence: 82%
“…1(c) and 1(d), edge atom pairs are counted. 39 The lattice parameter a 0 is the distance between the nearest atoms, or their projections onto a horizontal plane as depicted in Figs. 2(d) and 2(b) for a flat and low-buckled structure, respectively.…”
Section: Structures and Calculation Modelmentioning
confidence: 99%
“…In particular, armchair and zigzag edges are the most stable edge structures [16,23,24] while GQDs with zigzag edges are found to exhibit unusual magnetic [25][26][27] and optical [28][29][30][31][32] properties due to the presence of a degenerate band of states at the Fermi level. On the other hand, armchair edges do not lead to degenerate band of states at the Fermi level, hence, can be used as small model of bulk graphene which does not have edge states [33].…”
Section: Introductionmentioning
confidence: 99%
“…5,33,[36][37][38][39][40][41][42][43][44][45][46] These edge states have significant effects on low-energy electronic properties such as a decrease of the energy gap compared to structures with armchair termination or, when combined with broken sublattice symmetry, a creation of the degenerate shell of zero-energy states in the middle of the energy gap. 33,[40][41][42][43][44][45][46][47][48][49] It was shown that the degenerate shell survives when various types of disorder are present in the system. [44][45][46][47] The influence of an external magnetic field on the electronic properties of the graphene quantum dots was also studied.…”
Section: Introductionmentioning
confidence: 99%